التحولات الاقتصادية للدولة الجزائرية و انعكاساتها على الحياة الاجتماعية في منطقة وادي ريغ(1962- 1989 م) - الغول, الطاهر (University of Eloued جامعة الوادي, 2021)
تلخّصت الدراسة حول التحوّلات الاقتصاديّة للدولة الجزائريّة بعد الاستقلال، حيث انطلقت مسيرة الاقتصاد الوطني الجزائري من فكرة إحداث القطيعة مع الاقتصاد الاستعماري الكولونيالي واعتماد النهج الاشتراكي بناء على المرجعيّات التاريخيّة للثورة التحريريّة، خاصّة توصيات برنامج طرابلس 1962 وذلك من خلال تدشين نظام التسيير الذاتي وبداية التأميم والاقتصاد المركزيّ مما تميّز به عهد الرئيس أحمد بن بلّة (1962-1965م). لتدخل البلاد في مرحلة التأميمات الكبرى والاقتصاد المخطّط وسيطرة الدولة على أصول الثروة ووسائل الإنتاج ورفع شعار الثورات الصناعيّة والزراعيّة والثقافيّة ممّا طبع عهد الرئيس هواري بومدين (1965-1978م). ثم تأتي مرحلة الانفتاح وإعادة الهيكلة الاقتصاديّة بهدف إعطاء مساحة للّامركزيّة وفسح المجال للمراجعة والإصلاح في مختلف الميادين الاقتصاديّة وتمكين القطاع الخاص من الاستثمار والمبادرة، ومن ثمّ تخلّي الدولة عن النهج الاشتراكي والتحوّل من جديد نحو اقتصاد السوق والخيار الرأسمالي، وهذا ما اتسم به عهد الرئيس الشاذلي بن جديد (1979-1992م)، على أن فترة الدراسة تنتهي في حدود سنة 1989م. كل هذا كان له انعكاساتُه وتأثيراتُه على الحياة الاجتماعيّة بمنطقة وادي ريغ، حيث عرف المجتمع المحلّي بهذا الإقليم تطوّرات عميقة وتغيّرات اجتماعيّة وديموغرافيّة وإداريّة وفكريّة وثقافيّة وحتى على المستوى المجاليّ والجغرافيّ مُسايرةً لتلك التحوّلات الاقتصاديّة التي مرّت بها الدولة الجزائريّة المستقلّة. The study about the economic transformations of the Algerian state after independence have summarized, as the path of the Algerian national economy started from the idea of creating a break with the colonial economy and adopting the socialist approach based on the historical references of the liberation revolution, Especially the recommendations of the Tripoli program 1962. Through the inauguration of the system of self-management or (self-governance) and the beginning of nationalization and the central economy, that is what characterized the era of President Ahmed ben Bella (1962-1965). To enter the country to the major nationalizations stage and the planned economy, state control of the assets of wealth and means of production, and raising the slogan of industrial, agricultural and cultural revolutions, which dentified the era of President Houari Boumediene (1965-1978). Then comes the stage of openness and economic restructuring with the aim of giving space for decentralization and giving way to review and reform in various economic fields and enabling the private sector to invest and initiate, and then the state abandoned the socialist approach and a renewed shift towards a market economy and capitalist choice, and this is what characterized the era of President Chadli ben Djedid (1979-1992), provided that the study period ends within the year 1989 .. All of this had repercussions and effects on the social life of the Righ Valley region, where the community experienced in this region profound developments and social, demographic, administrative, intellectual, cultural, and even on the domain and geographical level in line with those economic transformations experienced by the independent Algerian state.
أطروحة دكتوراه في التاريخ تخصص تاريخ حديث ومعاصر
Keywords: التحوّلات الإقتصادية، الرئيس بن بلّة، الرئيس بومديَن ، الرئيس الشاذلي، التسيير الذاتي، التسيير الاشتراكي، إعادة الهيكلة ، منطقة وادي ريغ.; Economic transformations - President Ahmed ben Bella - self-governance - President Houari Boumediene- major nationalizations -President Chadli ben Djedid- Economic restructuring- the Righ Valley region